PEMBERDAYAAN POKDARWIS KAMPUNG EMBUNG WONOLOPO KOTA SEMARANG BERBASIS KEARIFAN LOKAL MENDUKUNG KAWASAN WISATA - dwi, Dwi Prastiyo Hadi; Riyanto, Riyanto; Sutrisno, Sutrisno (Jurnal Abdi Insani, 2024)
Wonolopo Tourism Village is a Thematic Village that supports tourism packages, with the presence of a reservoir, Wonolopo Village has more visitors, for that reason souvenirs are needed that are typical of Wonolopo Village, Wonolopo Village has agricultural potential in the form of cassava, sweet potatoes, bananas, aloe vera. In order to be more optimal, it will be processed into products that are typical of Wonolopo Village and can improve the community's economy. The purpose of this activity is to find solutions to the problems of the Wonolopo Village community with a community empowerment approach, so as to strengthen the community's potential and form a tourist village "Edupark and Agricultural Center". The results of the community service activities are (1) the community understands and supports the PKM program; (2) the formation of the Embong Wonolopo UMKM association; (3) the formation of the Embong Wonolopo Pokdarwis and the Layout (Master Plan) of the Embung Tourism Village to build the Embong Wonolopo tourist attraction, (4) the emergence of various snacks made from bananas, cassava, sweet potatoes, and hand sanitizers made from aloe vera (5) increasing income and prosperity of the community from the processing of local potential in the form of bananas, cassava, sweet potatoes and aloe vera into products that have a higher economic value. There is an increase in income, an increase in the quality of tourism products and services, as well as increasing business networks with various partners and the formation of online stores.